Developing of Tuwel Tourism Village, Bojong District, Tegal Regency - Septiani, Rina; Nurjanah, Nita; Thalib, Mukhtar (Indonesian Journal of Community Services Cel, 2022)
Tuwel Village, Bojong District, Tegal Regency has a great tourism potential, but the local community is not aware of this and has not been developed properly. The objectives of the activity are (1) developing the tourism potential, (2) empowering the Tuwel village community, (3) creating the tourism facilities in Tuwel village. The method used was the analysis of tourist attraction, analysis of tourism supporters, and analysis of the local communities. This community service was carried out with community partners in Tuwel Village, Bojong District, Tegal Regency. The result of this service is the optimization of the tourism potential by complementing the gate to a tourist attraction, helping the construction of the tourist counter of Sigeong Curug. As the result of this program, the community consciousness and Pokdarwis of Tuwel Village are increased and also the improving of the tourism facilities.